E-commerce Website for Small-scale Businesses with Neighborhood Shop and Product Recommendation System - Meghsham Kapure; Dnyanal Vedpathak; Soham Solat; B.D. Thorat (E-COMMERCE FOR FUTURE & TRENDS, 2022)
The fast and rising industry of e-commerce as well as m-commerce has made it easier to sell and buy things online, but it is a complicated and time-consuming procedure to do right from shipping to delivery to customers. Also, small-scale businesses would not be able to build marketing and selling infrastructure like tech e-commerce giants, gaining customers’ attention and providing services and product faster, more efficiently, and hustle-free experience with bare minimum cost and delivery charges and a better fit of products from their locality to support the seller and customer as well. Recommendation system plays a crucial role in this as it suggests relevant and possible selling item to the customers which are already selling on the platform. The most popular and widely utilised approaches for recommending products across various e-commerce platforms are collaborative filtering and content-based filtering. Using this technique, we can generate more and more sales with the platform. The proposed product suggestion system, with this addition, can make a significant difference in mainstream sales over both offline and online marketing. Getting the deliveries faster than ever before is also a great benefit of the project. Along with this, customers will be advised of small businesses that they may not have been able to reach owing to a lack of advertising and promotion tactics.